2006
DOI: 10.1021/jp0655221
|View full text |Cite
|
Sign up to set email alerts
|

Sum-over-States Calculation of the Specific Rotations of Some Substituted Oxiranes, Chloropropionitrile, Ethane, and Norbornenone

Abstract: A sum-over-states approach has been applied to the calculation of the specific rotations of several substituted oxiranes, 2-chloropropionitrile, and 30 degrees-rotated ethane. In each case, the first few excited states proved to have only a relatively small effect on the calculated specific rotation. It was necessary to use a very large number of excited states in order to achieve convergence with the results of the more direct linear response method. However, the latter does not give information on which exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 25 publications
7
64
0
1
Order By: Relevance
“…This finding is in qualitative agreement with an SOS analysis by Wiberg et al, [43] who showed with B3LYP/ aug-cc-pVDZ computations that the (partial) isotropic OR resulting from just the first excitation is more than 40 % larger in magnitude than the converged full linear response value. That is, higher excitations dampen the isotropic OR, and this dampening effect must also influence the characteristics of the OR tensor.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in qualitative agreement with an SOS analysis by Wiberg et al, [43] who showed with B3LYP/ aug-cc-pVDZ computations that the (partial) isotropic OR resulting from just the first excitation is more than 40 % larger in magnitude than the converged full linear response value. That is, higher excitations dampen the isotropic OR, and this dampening effect must also influence the characteristics of the OR tensor.…”
Section: Resultssupporting
confidence: 91%
“…The (perhaps fortuitously) good performance of B3LYP/aug-cc-pVDZ calculations for this molecule has been noted previously. [43,44] Wiberg et al [43] pointed out that much of the large magnitude of the optical rotation of 2 can be attributed to the intense CD of the longestwavelength excitation and the coupling of the C=O and the C=C chromophores. See also a discussion by Moscowitz from 1962.…”
Section: Resultsmentioning
confidence: 99%
“…This is obviously impossible and practical reasons dictate that only a finite number of electronic transitions can be used. In fact, it has been observed that the low‐lying valence and Rydberg transitions usually are not of major importance for evaluation of OR in the non‐resonant long wavelength region and the use of the first 25–30 transitions is generally sufficient . The computation on the first 30 excited states also allows us to take into account the contribution of transitions occurring below 200 nm, not experimentally visible because of the solvent cut‐off.…”
Section: Resultsmentioning
confidence: 99%
“…Before concluding this section, we notice that the method presented here shares some analogies with what proposed in the case of hindered rotations to obtain vibrational averages of molecular properties like the optical rotatory dispersion, which is connected to ECD by the Kramers‐Kronig relation . In Mort and Autschbach, however, only the soft mode is considered, while the other vibrational modes are not explicitly included in the calculation, being not important for a Boltzmann average.…”
Section: Theory and Computational Detailsmentioning
confidence: 99%